Tematizace vztahu člověka k Bohu v prózách Jaroslava Havlíčka (II) - Mlsova, Nella (Eslavística Complutense, 2003)
The paper, the first part of which was published in the former issue, deals on themes of relation between man and God in the prose of Jaroslav Havlíček. It illustrates the ways of interpretation of the theme in his selected works.